Case Study: SQL Tuning: IN Versus OR Versus Global Temporary Table - Liu, Henry H (Oracle Database Performance and Scalability, 2011)
<![CDATA[ This chapter contains sections titled: Context Test Program Observation 1: IN_CreateStatement is the Best Performer Observation 2: Batch Insert Saves Time Temptable Performed Better without an Index Hint than with an Index Hint Effects of APPEND Hint for Populating Temptable Effects of Number of Iterations OR and IN without the Index Hint Limitation on the Number of Literal Values and the Size of OR Statement Dealing with More Than 1000 Literal Values for an IN Based SQL Query A Recommendation for Dealing with 1000 Literal Value Limit in an IN Statement Summary Recommended Reading Exercises ]]>